Penerapan Konseling Kelompok Menggunakan Teknik Role Play untuk Mengurangi Tingkat Bullying - Lira Tegar Riyadi; Kusnadi Kusnadi; Bela Janare Putra (Journal of Society Counseling, 2025)
This research is entitled "Application of Group Counseling Using Role Play Techniques to Reduce the Level of Bullying at Utsman Said's Tahfidz House 26 Ilir Palembang". In the growth of a santri and santriwati, there are various kinds of upbringing in the way they are treated by parents and the surrounding environment, which becomes the driving force for every development that the santri and santriwati have. Bullying that occurs at Tahfidz House can disrupt the learning process, thereby creating an atmosphere that is less conducive to the development of santri and female students. Therefore, santri and female students need group counseling using role-play techniques to reduce the level of bullying that occurs at Tahfidz House. This research employs descriptive qualitative research methods in a field study, involving 6 santri and female students as research subjects. The data collection techniques utilized in this research include observation, interviews, and documentation. The analysis of the data is conducted using data collection analysis techniques, followed by data reduction and the presentation of conclusions and verification data. The research results show that the application of group counseling using role play techniques can have a positive impact on reducing bullying behavior at Tahfidz House. Role play techniques involve various situations related to bullying, both as victims, perpetrators, and witnesses, to increase understanding and empathy for the negative impacts of bullying and increase students' awareness of the importance of respecting each other, maintaining each other's feelings, and creating a safe and comfortable environment at Tahfidz House.